Analysis of Student Creativity in Developing Science Learning Media during the COVID-19 Pandemic - Ulya Wati; Woro Sri Hastuti; Ali Mustadi (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to ascertain (1) the inventiveness of university students in developing digital media for science education. (2) provides an overview of elementary science media applications that students can develop, and (3) discusses the obstacles students encountered while developing digital media for elementary science learning during COVID-19. This study took place at Yogyakarta State University and Makassar State University. The sample size for this study is 142 students, including 71 UNM students and 71 UNY students. The approach is descriptive with a quantitative component. Thus, the results demonstrated students' creativity in developing science media during the COVID-19 pandemic, as measured by five characteristics: fluency, flexibility, originality, elaboration, and sensitivity. Students can create media by using applications such as PowerPoint, Articulate Storyline, Flipbook Maker, Wondershare Filmora, and a variety of other supporting platforms (websites). However, students face obstacles in four areas when developing media, including fluency, flexibility, originality, and elaboration, namely (1) students continue to struggle with integrating science learning media into elementary school through the use of appropriate approaches/models/learning methods, (2) determining the variety of problem-solving strategies available to users of science learning media in elementary school, and (3) determining the variety of problem-solving strategies available to users of science learning media in elementary school. (3) difficulty identifying science learning media for elementary schools located in areas without internet access due to the COVID-19 pandemic and others.